Analyzing the prohibition of interfaith marriage in Indonesia: legal, religious, and human rights perspectives - M. Thahir Maloko; Sippah Chotban; Muhammad Ikram Nur Fuady; Hasdiwanti (Cogent Social Sciences)
The prohibition of interfaith marriage is stipulated in the Indonesian Marriage Law where this practice is considered valid when conducted according to the laws of each respective religion and belief. This is supported by the Compilation of Islamic Law, regulating the prohibition of interfaith marriage. This research aimed to analyze the prohibition of interfaith marriage using a qualitative methodology with normatively on the regulations and Indonesian Supreme Court Decision Number 1977/K/PDT/2017. The results showed that Supreme Court Justices reject the review of the rules governing interfaith marriage submitted by a couple (Islam and Christianity). This was because the concept violated the Human Rights Law, the Marriage Law, the Compilation of Islamic Law, and the Fatwa of the Indonesian Ulema Council. Furthermore, the decision was in conflict with human rights concerning an individual’s freedom to have beliefs and form a family. Pluralist groups also viewed this prohibition as more of a political nature under the guise of religion. Therefore, many interfaith couples preferred unregistered marriage abroad before recording in the Civil Registry Office, which represented a form of legal smuggling in Indonesia as the impact of perplex on this issue.